Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Cueto Santander, Brenda Isabel (2018)
The present work of professional sufficiency has as objective to realize a strategic plan for the Fast Retailing group and to evaluate its possible entrance to the Peruvian market with the brand UNIQLO. The Japanese giant is characterized mainly by the innovation and development of materials, and the basic design and little variation in style of its garments, as well as large-scale manufacturing. The analysis will be based on the fast fashion industry, belonging to the retail sector in the textile and footwear divisions. It is important to emphasize that, in Peru, the fast fashion industry is relatively new. It entered its operations with the entry of Zara in 2012, followed by other brands such as Forever 21 and H&M. Also, the case presents analysis of historical and current information of several case studies, news, websites and official press releases of the company. Firstly, an analysis of the group's business model will be made in order to establish the bases for the development of the following points to be dealt with. This will be followed by an evaluation of both strengths and weaknesses, as well as the competitive advantage it has achieved since entering the sector. Subsequently, an analysis will be made of the fast fashion industry and the retail sector in the Peruvian territory. The purpose of this evaluation is to establish a clear panorama and determine opportunities and threats for Fast Retailing in its entry into the Peruvian market in the coming years. In addition, a strategic implementation proposal will be made based on the points worked previously, the redefinition of the business units and control mechanisms necessary to successfully enter the Peruvian market. Finally, the main conclusions and recommendations of the case, which were reached during the present investigation, will be presented.